DISENGAGE Registry. (November 2020) - Pellicano, Mariano; Ciccarelli, Giovanni; Xaplanteris, Panagiotis; Di Gioia, Giuseppe; Milkas, Anastasios; Colaiori, Iginio; Heyse, Alex; Van Durme, Frederik; Vanderheyden, Marc; Bartunek, Jozef; De Bruyne, Bernard; Barbato, Emanuele
Abstract : Background: During fractional flow reserve (FFR) measurement, the simple presence of the guiding catheter (GC) within the coronary ostium might create artificial ostial stenosis, affecting the hyperemic flow. We aimed to investigate whether selective GC engagement of the coronary ostium might impede hyperemic flow, and therefore impact FFR measurements and related clinical decision-making. Methods: In the DISENGAGE (Determination of Fractional Flow Reserve in Intermediate Coronary Stenosis With Guiding Catheter Disengagement) registry, FFR was prospectively measured twice (with GC engaged [FFReng ] and disengaged [FFRdis ]) in 202 intermediate stenoses of 173 patients. We assessed (1) whether ΔFFReng –FFRdis was significantly different from the intrinsic variability of repeated FFR measurements (test-retest repeatability); (2) whether the extent of ΔFFReng –FFRdis could be clinically significant and therefore able to impact clinical decision-making; and (3) whether ΔFFReng –FFRdis related to the stenosis location, that is, proximal and middle versus distal coronary segments. Results: Overall, FFR significantly changed after GC disengagement: FFReng 0.84±0.08 versus FFRdis 0.80±0.09, P <0.001. Particularly, in 38 stenoses (19%) with FFR values in the 0.81 to 0.85 range, GC disengagement was associated with a shift from above to below the 0.80 clinical cutoff, resulting into a change of the treatment strategy from medical therapy to percutaneous coronary intervention. The impact of GC disengagement was significantly more pronounced with stenoses located in proximal and middle as compared with distal coronary segments (ΔFFReng –FFRdis, proximal and middle 0.04±0.03 versus distal segments 0.03±0.03; P =0.042). Conclusions: GC disengagement results in a shift of FFR values from above to below the clinical cutoff FFR value of 0.80 in 1 out of 5 measurements. This occurs mostly when the stenosis is located in proximal and middle coronary segments and the FFR value is close to the cutoff value. Abstract : Supplemental Digital Content is available in the text.